Isolation and characterization of the secondary metabolites: Antidesma ghaesembilla gaertn - Gonzales, Rhanney L. (Animo Repository, 2017)
Antidesma ghaesembilla, also known as arocep in Ilokano or binayuyu in Tagalog, is a small deciduous tree found in mountainous area of Central and Northern Luzon. The fruits are edible and have a resemblance to blackcurrant. The leaves and bark are utilized as herbal medicines for fever, cough and rheumatism. Chemical investigation of the dichloromethane extracts of Antidesma ghaesembilla Gaertn. afforded b-friedelinol (AG21L), lupeol (AG13L), squalene (AG9LA), polyprenol (AG12L), b-sitosterol (AG19L) and long-chain hydrocarbons (AG2L) from the leaves; and b-sitosterol (AGF2B) and triacylglycerols (AGF1) from the fruit. The structure of 1 was elucidated by extensive 1D and 2D NMR spectroscopy, while those of 2-7 were identified by comparison of their NMR data with literature data. This is the first report on the isolation of these compounds from A. ghaesembilla.